(untitled) (Historia, 2021)
Although there has traditionally been more accent on violence and war between black and white in South African historiography, relations in the central districts of the South African Republic (ZAR) were dynamic in their own right. In the article an analysis is made of race relations issues, particularly relative to land and labour. Documents of a little known commission of 1871 were consulted extensively for information. An outstanding feature of the dynamics of the situation was that the blacks responded in an innovative manner on the pressures that were applied on them.